2005
DOI: 10.1007/s10334-005-0020-0
|View full text |Cite
|
Sign up to set email alerts
|

Brain tumor evaluation and segmentation by in vivo proton spectroscopy and relaxometry

Abstract: A new methodology has been developed for the evaluation and segmentation of brain tumors using information obtained by different magnetic resonance techniques such as in vivo proton magnetic resonance spectroscopy (1HMRS) and relaxometry. In vivo 1HMRS may be used as a preoperative technique that allows noninvasive monitoring of metabolites to identify the different tissue types present in the lesion (active tumor, necrotic tissue, edema, and normal or non-affected tissue). Spatial resolution for treatment con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…The equally spaced sampling of the magnetization decay allows for a polynomial representation of each data point according to (3). If it is assumed [3], [4], that at most 3 tissues are present in each voxel; normal or unaffected tissue, lesion tissue and cerebrospinal fluid, CSF, a set of non linear polynomial equations [6], [7] can be written:…”
Section: Non Linear Polynomial Equationsmentioning
confidence: 99%
See 4 more Smart Citations
“…The equally spaced sampling of the magnetization decay allows for a polynomial representation of each data point according to (3). If it is assumed [3], [4], that at most 3 tissues are present in each voxel; normal or unaffected tissue, lesion tissue and cerebrospinal fluid, CSF, a set of non linear polynomial equations [6], [7] can be written:…”
Section: Non Linear Polynomial Equationsmentioning
confidence: 99%
“…Tests performed with synthetic data composed of linear combinations of up to 3 exponential functions demonstrated that solutions of equation (16) subjected to conditions (5) always yielded the right number of exponentials. For the simulations, a set of 3 relaxation rates was chosen according to those expected for tumoral lesions in brain [3], [4], i.e., 2 s -1 for necrosis or CSF, 7 s -1 for tumoral tissue and 12 s -1 for normal or unaffected tissue. The results of the simulation assuming that each relaxation rate exhibits a Gaussian distribution around its mean value are shown in Figure 1.…”
Section: Simulationsmentioning
confidence: 99%
See 3 more Smart Citations